SPECTRUM OF ADRENAL INFECTIONS – FROM SOFT TO HARD: CASES OF ADRENAL ABSCESS AND CALCIFICATION - Nasution, Muhammad Habib Nasution Zulpan; Mokti, Abdullah Shamshir Abd; Azni, Khaulah Karimah; Handar, Nor Fauziah Muhamad; Mohamad, Masni (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Adrenal infections can present in a spectrum from adrenalitis to abscess and calcification. It may either affect the adrenals unilaterally or bilaterally. We present two cases of adrenal infections: a unilateral adrenal abscess following ERCP and a bilateral adrenal calcification due to Histoplasmosis. CASE The first case is a 54-year-old male, with a history of alcoholism and diabetes, who presented with abdominal pain. Initial CT-abdomen showed chronic pancreatitis with a right adrenal lesion measuring 4.8 cm. ERCP done showed pancreatitis with infected pseudocyst. However, he presented back 2 months later with fever, abdominal pain and constitutional symptoms. CT-abdomen revealed a small liver abscess and a right adrenal abscess measuring 9 cm with an average HU of 61. He was treated with antibiotics for 8 weeks and underwent abscess drainage. The hormonal work-up was within normal range with adrenal insufficiency ruled out. All bacterial, tuberculous and fungal work-up were negative. A repeat CT of the abdomen after 4 months showed a residual adrenal abscess measuring 4.8 cm and a right adrenalectomy was scheduled. The second case is a 45-year-old male, a smoker with hypertension, who presented with constitutional symptoms, skin darkening, fever and features of adrenal crisis. Steroids and antibiotics were started. CT of the abdomen showed enlarged and calcified bilateral adrenals measuring 5 cm. Primary adrenal insufficiency was confirmed biochemically. CT-guided biopsy showed fibrous and necrotic tissue and PAS, GMS and Ziehl-Nielsen stains were negative. Adrenal tissue PCR was positive for Histoplama capsulatum and a diagnosis of adrenal histoplasmosis was made. The patient underwent a two-week treatment with Amphotericin B and continued with oral Itraconazoleplanned for 1 year. He showed improved general health and increased weight. Repeat CT of the adrenals after 3 months showed no significant change. CONCLUSION Adrenal infections have various presentations and can affect both immunocompetent and immunocompromised patients. Treatment of the underlying organism with antimicrobial therapies and steroid replacement is key to avoiding significant morbidity and mortality